In Vivo Computed Tomography Direct Volume Rendering of the Anterior Ethmoidal Artery: A Descriptive Anatomical Study - Filippo Cascio; Alberto Cacciola; Simona Portaro; Gianpaolo Antonio Basile; Giuseppina Rizzo; Andrè Wady Debes Felippu; Alexandre Wady Debes Felippu; Antongiulio Bruschetta; Carmelo Anfuso; Felice Cascio; Demetrio Milardi; Alessia Bramanti (International Archives of Otorhinolaryngology, 2020)
Introduction The clinical relevance of the anatomy and variations of the anterior ethmoidal artery (AEA) is outstanding, considering its role as a landmark in endoscopic surgery, its importance in the therapy of epistaxis, and the high risks related to iatrogenic injuries. Objective To provide an anatomical description of the course and relationships of the AEA, based on direct computed-tomography (CT)-based 3D volume rendering. Methods Direct volume rendering was performed on 18 subjects who underwent (CT) with contrast medium for suspected cerebral aneurism. Results The topographical location of 36 AEAs was assessed as shown: 10 dehiscent (27.8%), 20 intracanal (55.5%), 6 incomplete canals (16.7%). Distances from important topographic landmarks are reported. Conclusion This work demonstrates that direct 3D volume rendering is a valid imaging technique for a detailed description of the anterior ethmoidal artery thus representing a useful tool for head pre-operatory assessments.